Using Inexpensive Software-Defined Radios as GPS Receivers in a Ground-Based Augmentation System - Taylor, Jaxon (My University, 2022)
Ground Based Augmentation Systems (GBAS) are used to augment Global Positioning Systems (GPS) signals to make the position solutions significantly more accurate and precise. The systems have been studied and demonstrated before, however, they would typically use dedicated GPS receivers. These receivers are typically expensive and lack the ability to be customized for different situations. This thesis attempts to use a software-defined radio (SDR) using a software called Global Navigation Satellite Systems-Software Defined Receiver (GNSS-SDR) to replace these dedicated GPS receivers. Doing this requires multiple GNSS-SDR receivers to output the data in real-time to a central GBAS computer for real-time computations. This is done using the User Datagram Protocol (UDP) output functionality of the GNSS-SDR software. The output then needs to be received on the GBAS computer and decoded. A novel method for decoding the Google Protocol Buffer encoded UDP messages is used for efficient LabVIEW decoding. The outputs are then tested using an existing Closed-Loop Ground Based Augmentation System (CL-GBAS) program. An analysis of the raw pseudorange values of two different SDRs and certified GPS receivers is then performed. The research performed in thesis will ideally be used as a stepping stone for more thorough analysis of different SDRs and the GNSS-SDR program in an attempt to make SDRs an effective receiver for GBAS purposes.
Keywords: Engineering, Electronics and Electrical.; Computer Science.; Engineering, General.